2023
DOI: 10.1002/hed.27398
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oral squamous cell carcinoma focusing on cases unaffected by smoking and drinking: A multicenter retrospective study

Abstract: Background: Some oral squamous cell carcinoma (OSCC) cases are unaffected by smoking or drinking. This study aimed to clarify distinctive groups among OSCC patients and examine the characteristics of multiple primary carcinomas (MPCs).Methods: We analyzed data from 970 patients. The patients were divided into three groups: all individuals <45 years (<45 y), smokers/drinkers ≥45 years (SD ≥45 y), and non-smokers/non-drinkers ≥45 years (NSND ≥45 y).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Clinical features such as the location and size of the tumor are crucial factors in determining the progression and prognosis of the disease. Our observations revealed that the buccal mucosa was the most frequent site of tumor development, followed by the tongue, contrary to the literature, which states that the tongue is the most common site [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Clinical features such as the location and size of the tumor are crucial factors in determining the progression and prognosis of the disease. Our observations revealed that the buccal mucosa was the most frequent site of tumor development, followed by the tongue, contrary to the literature, which states that the tongue is the most common site [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…According to data from 970 patients, the floor of the mouth, soft palate, gingiva, buccal mucosa, and hard palate were the sites with the highest prevalence of OSCC, accounting for around 50% of all the cases [17].…”
Section: Discussionmentioning
confidence: 99%
“…11 Large-sample studies have consistently shown that regular consumption of vegetables, citrus fruits, sh, and vegetable oils is the main feature of a low-risk diet for oral cancer, after adjusting for smoking and alcohol intake. 12 Patients and medical staff having greater awareness of the risk factors for oral cancer can lead to early diagnosis, which in turn will help improve the survival of oral cancer patients to the greatest extent. Moreover, there is a lack of research on the risk factors for oral cancer in young people.…”
Section: Discussionmentioning
confidence: 99%